Light‐Triggered Control of Glucocerebrosidase Inhibitors: Towards Photoswitchable Pharmacological Chaperones. Issue 19 (1st March 2023) - Clemente, Francesca; Davighi, Maria Giulia; Matassini, Camilla; Cardona, Francesca; Goti, Andrea; Morrone, Amelia; Paoli, Paolo; Tejero, Tomás; Merino, Pedro; Cacciarini, Martina
Abstract: Piperidine‐based photoswitchable derivatives have been developed as putative pharmacological chaperones for glucocerebrosidase (GCase), the defective enzyme in Gaucher disease (GD). The structure‐activity study revealed that both the iminosugar and the light‐sensitive azobenzene are essential features to exert inhibitory activity towards human GCase and a system with the correct inhibition trend (IC50 of the light‐activated form lower than IC50 of the dark form) was identified. Kinetic analyses showed that all compounds are non‐competitive inhibitors (mixed or pure) of GCase and the enzyme allosteric site involved in the interaction was identified by means of MD simulations. A moderate activity enhancement of mutant GCase assessed in GD patients' fibroblasts (ex vivo experiments) carrying the most common mutation was recorded. This promising observation paves the way for further studies to improve the benefit of the light‐to‐dark thermal conversion for chaperoning activity. Abstract : Photoactive pairs with stronger affinity for GCase in the light‐activated form than in the thermally‐deactivated one were identified for the development of pharmacological chaperones. The study shows that enantiopure trihydroxypiperidine and azobenzene are key‐units in the inhibition process of human GCase enzyme and that photoswitchable iminosugars bind at an allosteric site.